Tetrahydroxystilbene Glucoside Ameliorates Infrasound-Induced Central Nervous System (CNS) Injury by Improving Antioxidant and Anti-Inflammatory Capacity. (11th January 2020) - Zhou, Xuanxuan; Yang, Qian; Song, Fan; Bi, Linlin; Yuan, Jiani; Guan, Shaoyu; Yang, Qi; Wang, Siwang
Abstract : Background . Infrasound is a major threat to global health by causing injuries of the central nervous system (CNS). However, there remains no effective therapeutic agent for preventing infrasound-caused CNS injury. 2, 3, 5, 4 ′ -Tetrahydroxystilbene-2-O- β -D-glycoside (THSG) exerts protective function against CNS injuries and may have beneficial effects on infrasound-induced CNS impairment. Methods . A mouse model with CNS (oxidative stress-induced inflammation and neuronal apoptosis) injuries was established when the mouse was exposed to the infrasound of 16 Hz at 130 dB for 2 h each day and the duration of treatment was 8 d. The mice were divided into the control (CG, healthy mice), the model (MG, model mice), and the THSG (EG, experimental group, model mice treated with THSG) groups. The learning and memory impairments caused by infrasound were examined using a Morris water maze test. Lipid profiles, antioxidant biomarkers, and inflammatory cytokines in hippocampus tissue were measured by using corresponding ELISA kits. Meanwhile, BCL-2/BAX/caspase-3 signaling pathway was measured in the hippocampi and prefrontal cortex of the mouse brain using real-time qPCR and Western blot. Nissl's stain was used to measure neuronal necrosis in the hippocampi and prefrontal cortex of the mouse brain. Results . THSG significantly ameliorated the learning and memory impairments caused by infrasound. On the other hand, THSG improved lipid profiles, increased antioxidant properties by affecting the levels of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), and malondialdehyde (MDA), and displayed anti-inflammatory action via the downregulation of IL- (interleukin-) 6, IL-8, IL-10, TNF- (tumor necrosis factor-) α, and hs-CRP (high-sensitivity C-reactive protein) in the hippocampal tissues of the mouse model (P < 0.05 ). Additionally, Nissl's stain showed that THSG inhibited infrasound-induced neuronal necrosis in the hippocampi and prefrontal cortex. Besides, THSG exerted antiapoptosis function by upregulating the level of Bcl-2 and downregulating the levels of BAX and caspase-3 in the hippocampi. Conclusion . THSG may be an effective anti-infrasound drug against CNS injury by improving antioxidant, anti-inflammatory, antiapoptosis, and antinecrosis capacities. Further research is still needed to confirm the exact molecular mechanism.